The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1177/0969733011423409
|View full text |Cite
|
Sign up to set email alerts
|

Influencers of ethical beliefs and the impact on moral distress and conscientious objection

Abstract: Considering a growing nurse shortage and the need for qualified nurses to handle increasingly complex patient care situations, how ethical beliefs are influenced and the consequences that can occur when moral conflicts of right and wrong arise need to be explored. The aim of this study was to explore influencers identified by nurses as having the most impact on the development of their ethical beliefs and whether these influencers might impact levels of moral distress and the potential for conscientious object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 38 publications
2
76
0
4
Order By: Relevance
“…Pendry (2007) identified moral distress as the physical or emotional suffering that is experienced when constraints (internal or external) prevent one from following the course of action that one believes is right. According to Rittenmeyer and Huffman (2009) (Davis, Schrader, & Belcheir, 2012).…”
Section: Moral Distress Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pendry (2007) identified moral distress as the physical or emotional suffering that is experienced when constraints (internal or external) prevent one from following the course of action that one believes is right. According to Rittenmeyer and Huffman (2009) (Davis, Schrader, & Belcheir, 2012).…”
Section: Moral Distress Definitionmentioning
confidence: 99%
“…Rittenmeyer and Huffman (2009) identified causes of moral distress as including unrecognized power hierarchies, inability to influence medical decisions related to the care of the patient, inability to advocate for the patient, and institutional constraints. Endof-life issues, staffing patterns, nurse-physician conflicts, inadequate resources, and protection of human rights and dignity were also identified as potential factors that would cause moral distress (Davis, Schrader, & Belcheir, 2012 (Rice et al, 2008).…”
Section: Moral Distress: Etiology Contributors and Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Cusveller [18] sought to explain how the beliefs and values of Calvinism would inform a Calvinist nurse's practice and Atkinson [19] found in her empirical study on Muslim nurses in Kuwait, that their religion could not be separated from the nursing practice that they delivered. Davis et al [20] found that nurses whose ethical beliefs were mainly formed by religious beliefs, tended to experience higher degrees of moral distress in their delivery of nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…professional's, personal, ethical beliefs are at odds with established, societal norms of health care provision (Catlin et al 2008;Davis, Schrader and Belcheir 2012;Ford, Fraser and Marck 2010;Morton and Kirkwood 2009;Wicclair 2011). An ethical option available to healthcare professionals concerned with maintaining their moral integrity (personal and professional congruence) is to voice a conscientious objection to address their ethical dilemmas over providing and/or participating in a particular aspect of care provision that conflicts with their personal, ethical position (Canadian Nurses Association [CNA] 2008; Lachman 2014; Oxford English Dictionary [OED] 2016).…”
mentioning
confidence: 99%